Growth of Capital Market in Nepal: Impact on Capitalization, GDP and NEPSE Index - Chalise, Dhan Raj (Saptagandaki Journal, 2020)
The capital market plays an importance role in an economy and provides the opportunity to the investor for the mobilization and channelization of funds. Nepalese capital market is in growing and improving phase. The objective of this study is to analyze the evaluation of the existing status of the capital market in term of its composition of types of the capital market and to examine the impact of capital mobilization in Gross Domestic Product (GDP) and to examine the contribution of capital market in financial resources and GDP. Besides, the study examines the share transaction in Nepal Stock Exchange (NEPSE) and its impact on NEPSE Index. The study period of 2000/01 to 2018/19 has been used for study purposes. Through the use of descriptive research design, the trends of capital market development track after 2000/01 to present status has been presented. Secondary data are analyzed through the use of regression and other descriptive statists to convert the information into data. The result indicates that the ordinary shares in the primary capital market and market capitalization in the secondary market has significant contribution for the capital market in Nepal. Also, the study reveals that there is a significant and positive impact of capital mobilization on GDP and the number of share transactions on the NEPSE Index in the Nepalese capital market. Hence there is a significant contribution of the capital market for financial resources mobilization and GDP of Nepal. The study reports for modernization and systematization of the capital market need more optimal efforts from concerned stakeholders.